Pregnant women's retention and associated health facility characteristics in the prevention of mother-to-child HIV transmission in Indonesia: cross-sectional study. Issue 9 (24th September 2020) - Lumbantoruan, Christina; Kelaher, Margaret; Kermode, Michelle; Budihastuti, Endang
Abstract : Objectives: Despite the national effort to integrate the Prevention of Mother-to-Child Transmission (PMTCT) programme into antenatal care clinics in Indonesia, the rate of mother-to-child HIV transmission remains high. This national study was conducted to describe PMTCT programme performance and to identify health facility characteristics associated with this performance in order to inform programme planning and policy development. Design: A retrospective cross-sectional study in December 2017. Setting: All health facilities providing PMTCT programmes in Indonesia. Participants: All health facilities registering at least one woman in antenatal care in 2017. Intervention: PMTCT data extraction from the national reporting system on HIV/AIDS and government reports. Outcomes: Women retention in the PMTCT programme for at least 3 months and associated health facility characteristics. Results: A total of 373 health facilities registering 6502 HIV-positive women in antenatal care were included in the analysis. One-third of women (2099) never started antiretroviral treatment. Of the 4403 women who started, 2610 (57%) were retained; 462 (10%) were not retained; and the retention status of 1252 (28%) women referred out of the health facilities was unknown. Compared with primary health centres, hospitals were more likely to retain women (OR=2.88, 95% CI 2.19 to 3.79). The odds of retention were higher in hospital types A and B (OR=3.89, 95% CI 3.19 to 4.76), located within concentrated HIV epidemic areas (OR=2.09, 95% CI 1.83 to 2.38) and a high-priority area for the HIV programme (OR=1.83, 95% CI 1.60 to 2.09). We observed no differential retention between women who initiated PMTCT under different options (B+/non-B+). Conclusions: We observed low retention of HIV-positive pregnant women in the PMTCT programme in Indonesia in 2017. Additional efforts are needed to improve women's retention in the PMTCT programme. Retention could be increased through the delivery of PMTCT programmes by replicating strategies implemented at hospital types A and B located in concentrated HIV epidemic areas where an HIV programme is a high priority.